Analisis Pengaruh Pertumbuhan Ekonomi, Pengangguran Dan Kemiskinan Terhadap Ketimpangan Pendapatan Di Provinsi Kalimantan Tengah Tahun 2016-2020 - Deny Anugrah; Alexandra Hukom (Dharma Ekonomi, 2023)
This study aims to investigate how much influence three factors have on income inequality in Central Kalimantan Province, namely economic growth, the unemployment rate, and the poverty rate. The descriptive quantitative method is one of the methods used in statistical data analysis. It shows that the unemployment rate and poverty level significantly affect income inequality in Central Kalimantan, while economic growth has no significant effect. However, it is essential to remember that other factors affecting income inequality in Central Kalimantan are not included in the research model. Based on the analysis results in this study, there is a significant relationship between the independent variables, namely the unemployment rate and the poverty rate, with the dependent variable. Namely income inequality (Gini Ratio) in 13 regencies/cities in Central Kalimantan Province. However, the economic growth variable has no significant effect on income inequality. These results were obtained using the Random Effect Model method and the t-test statistic. Therefore, it is advisable to consider the unemployment and poverty rates in formulating policies to reduce income inequality in Central Kalimantan. However, it is essential to remember that other factors affect income inequality that are not included in the research model, so further research is needed to deepen understanding of these factors.